2013
DOI: 10.1016/b978-0-12-401676-7.00005-x
|View full text |Cite
|
Sign up to set email alerts
|

Drug Resistance Mediated by AEG-1/MTDH/LYRIC

Abstract: AEG-1/MTDH/LYRIC has been shown to promote cancer progression and development. Overexpression of AEG-1/MTDH/LYRIC correlates with angiogenesis, metastasis and chemoresistance to various chemotherapy agents in cancer cells originating from a variety of tissues. In this review article, we focus on the role of AEG-1/MTDH/LYRIC in drug resistance. Mechanistic studies have shown that AEG-1/MTDH/LYRIC is involved in classical oncogenic pathways including Ha-Ras, myc, NFκB and PI3K/Akt. AEG-1/MTDH/LYRIC also promotes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 81 publications
(136 reference statements)
5
64
1
Order By: Relevance
“…Downregulation of N-cadherin and snail, upregulation of E-cadherin, and translocation of β-catenin by depletion expression of MTDH in HCC cell lines indicates that MTDH may promote HCC metastasis through the induction of the epithelialmesenchymal transition (EMT) process [47,48]. Moreover, MTDH overexpression was correlated with clinicopathologic characters including cell proliferation, invasion, metastasis, chemoresistance, angiogenesis and poor clinical outcome [40,49,50]. A gradual increase in MTDH expression in normal liver tissue to hepatitis B and HBV-related HCC tissue levels was observed [51].…”
Section: Mechanisms Of Mtdh Overexpression In Hccmentioning
confidence: 95%
See 2 more Smart Citations
“…Downregulation of N-cadherin and snail, upregulation of E-cadherin, and translocation of β-catenin by depletion expression of MTDH in HCC cell lines indicates that MTDH may promote HCC metastasis through the induction of the epithelialmesenchymal transition (EMT) process [47,48]. Moreover, MTDH overexpression was correlated with clinicopathologic characters including cell proliferation, invasion, metastasis, chemoresistance, angiogenesis and poor clinical outcome [40,49,50]. A gradual increase in MTDH expression in normal liver tissue to hepatitis B and HBV-related HCC tissue levels was observed [51].…”
Section: Mechanisms Of Mtdh Overexpression In Hccmentioning
confidence: 95%
“…MTDH might function as a RNA binding protein to regulate the levels of important DNA repair factors at the post-transcriptional level. Previous work has shown that MTDH can promote translation of the multiple drug resistance gene MDR1 and the angiogenesis gene factor XII (FXII) [36,39,40]. Therefore, targeting MTDH might impair the ability of cancer cells to rapidly repair their DNA and increase therapeutic efficacy.…”
Section: Role Of Mtdh As An Rna Binding Protein In Drug Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have identified that AEG-1 serves a crucial role in tumor progression, including transformation, evasion of apoptosis, invasion, metastasis and chemoresistance (25,26). AEG1 has been reported to be associated with the activation of several signaling pathways including phosphoinositide 3-kinase (PI3K)/protein kinase B (AKT) and nuclear factor (NF)κB (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…; also known as AEG-1 and 3D3/LYRIC) has been implicated in many cancer-related processes, including cellular proliferation, survival, invasion, chemoresistance, and metastasis (1)(2)(3). MTDH is located on chromosome 8q22, a region that is frequently amplified in cancers and is correlated with poor survival in patients with breast cancer and hepatocellular carcinoma (4).…”
mentioning
confidence: 99%